POTENTIALS OF INTERACTIVE TEACHING TECHNIQUES TO TRAIN EXPERTS IN PHARMACY - A. V. Krikova; T. V. Anashchenkova; N. A. Pavlyutchenkova; T. V. Nikolaeva; V. M. Zaytseva (Фармация и фармакология (Пятигорск))
Various interactive teaching methods and techniques are extensively used in modern higher schools. Their implementation is considered to be one of the most significant and efficient ways to improve quality of pharmaceutical professional training. Efficiency of these interactive techniques applied at the Department of Economics and Management of Pharmaceutical Business of Smolensk State Medical University has been comprehensively investigated and assessed. Obtained results are presented in the paper, as well as students’ survey data as consumers of educational services. Fifth year full-time students were involved into the study. Students’ awareness on potentials and significance of applied interactive teaching methods, as well as their interest in innovative forms to gain professional knowledge comprised 93.3%. Potentials of interactive techniques to teach students to deal with a diversity of real life practical professional tasks and problems are particularly emphasized in the study (86.7% students).